PELAKSANAAN SIDANG PERADILAN PIDANA SECARA ONLINE PADA MASA PANDEMI COVID-19 TERHADAP PEMBUKTIAN DALAM PERSIDANGAN (Studi Penelitian di Pengadilan Negeri Lhokseumawe) - Fakraiza F; Muhammad Nur; Harun Harun (JURNAL ILMIAH MAHASISWA FAKULTAS HUKUM UNIVERSITAS MALIKUSSALEH, 2022)
The purpose of this study is to find out and explain the legal position of the online trial in the evidentiary process at the Lhokseumawe District Court, to find out and explain the power of evidence through online media at the Lhokseumawe District Court, and to know and explain the obstacles in evidence in the trial at the online criminal justice trial at the Court. Lhokseumawe country. The implementation of online criminal trials which are implemented based on a joint agreement between the Minister of Law and Human Rights, the Attorney General's Office and the Supreme Court can create a huge potential for the loss of the purpose of finding material justice in criminal cases. The process of examining criminal cases in court requires high precision/accuracy in examining facts which will then be reviewed with the application of the law. If the facts cannot be observed, then precise justice will be difficult to find, in fact there will be a neglect of justice. The research method of this thesis uses an empirical juridical research method with a statutory and case approach. The nature of the research used is descriptive. Sources of data used are primary data and secondary data. The results show that the legal position of the online trial in the evidentiary process at the Lhokseumawe District Court remains in accordance with the provisions issued by the Government as regulated in PERMA No. 4 of 2020 concerning Administration and Trial of Criminal Cases in Courts Online provides 2 (two) alternatives for conducting trials in criminal cases, namely offline and online. The power of evidence through online media at the Lhokseumawe District Court, where the quality of evidence in online criminal trials will be well maintained if the online trial continues to uphold the principle of doe process of law. Online criminal trials must be able to guarantee and ensure a transparent and accountable trial by minimizing all risks and crucial problems, especially in the evidentiary process. It is hoped that a law will be formed that regulates online criminal trials at a certain time. So that the online criminal case trial runs smoothly, obeys the principles in accordance with the applicable legal system in Indonesia.